The experience of art: Between Arthur Schopenhauer and Sigmund Freud - Hammad, Sarah (AUC Knowledge Fountain, 2018)
This thesis aims to juxtapose Freud's and Schopenhauer's doctrines, in the hopes of reaching a richer understanding of both thinkers. Both Freud and Schopenhauer believed that the way we viewed the world and ourselves was lacking, to a certain extent even distorted, and that such lack was due to our constitutional focus on ourselves, a focus developed from the absolute need for self-preservation. They both also called for a truer less distorted form of knowledge, a knowledge that could reach the essence of ourselves and therefore of the world. This thesis attempts to bring those two daring minds closer together in order for such a mutual augmentation to occur. The focal point of contact between the two will be the experience of art.